2011
DOI: 10.1007/s00421-011-2053-6
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced muscle damage and the repeated bout effect: evidence for cross transfer

Abstract: We examined whether a prior bout of eccentric exercise in the elbow flexors provided protection against exercise-induced muscle damage in the contralateral arm. Fifteen males (age 22.7 ± 2.1 years; height 178.6 ± 6.8 cm, mass 75.8 ± 9.3 kg) were randomly assigned to two groups who performed two bouts of 60 eccentric contractions (30°/s) separated by 2 weeks: ipsilateral (n = 7, both bouts performed in the same arm), contralateral (n = 8, one bout performed in each arm). Strength, muscle soreness and resting ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
75
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 62 publications
(80 reference statements)
7
75
2
1
Order By: Relevance
“…The authors also reported that the attenuation in markers of muscle damage in the contralateral group were smaller when compared to the group that performed both bouts with the ipsilateral arm. 54 Another study by Starbuck and Eston 55 found similar results. They had subjects perform six sets of 10 maximal eccentric contractions of the elbow flexors with the ipislateral arm during the first bout.…”
Section: Repeated Bout Effectsupporting
confidence: 70%
See 1 more Smart Citation
“…The authors also reported that the attenuation in markers of muscle damage in the contralateral group were smaller when compared to the group that performed both bouts with the ipsilateral arm. 54 Another study by Starbuck and Eston 55 found similar results. They had subjects perform six sets of 10 maximal eccentric contractions of the elbow flexors with the ipislateral arm during the first bout.…”
Section: Repeated Bout Effectsupporting
confidence: 70%
“…In addition, the cross-transfer repeated bout effect demonstrates that part of the repeat bout effect is produced irrespective of mechanical damage. This protective effect is most likely provided through neural mechanisms as suggested by Starbuck and Eston 55 . A complete understanding, however, of the involvement of the neural system in producing this repeated bout effect is still not clear.…”
Section: Repeated Bout Effectmentioning
confidence: 99%
“…In addition to the lack of data on the damage response in female athletes, much of the existing 73 literature investigating EIMD employs damage protocols that lack specificity to a sporting 74 context and are often eccentric biased (5,7,(17)(18)(19)(20)(21), and in isolated muscle groups (4,7, 18). Intermittent sports, such as soccer, rugby and basketball that require periods of high 76 intensity, repeated sprint activity and changes of velocity (22) and direction (23), elicit 77 significant muscle damage and prolonged decrements in function.…”
mentioning
confidence: 99%
“…For example, Howatson and Van Someren (2007) reported smaller increases in creatine kinase activity, delayed onset muscle soreness (DOMS), and decreases in muscle strength after a repeated bout of eccentric exercise on both the contralateral and ipsilateral elbow flexors with a greater attenuation of these muscle damage markers for the ipsilateral limb. More recently, Starbuck and Eston (2012) showed that strength loss and muscle soreness after the second eccentric exercise of the elbow flexors were attenuated for the contralateral arm, but median frequency was decreased in the second bout similarly between the ipsilateral and contralateral arms, suggesting a centrally mediated, neural adaptation. Furthermore, Xin et al (2014) reported an attenuated increase in nuclear factor-kappa B, an important regulator of muscle inflammation, after a second bout of eccentric exercise by the contralateral leg.…”
Section: Introductionmentioning
confidence: 97%
“…In the present study, TA muscle was chosen due to its muscle action, fiber composition, and activation profile (Johnson et al 1973;Madeleine et al 2006) and also because of its appropriateness for NWR recordings (Andersen 2007). Since previous studies have reported attenuated RBE in the contralateral elbow flexors muscle when compared with the ipsilateral side (Howatson and Van Someren 2007;Starbuck and Eston 2012), the secondary bout of eccentric exercise was therefore hypothesized to result in smaller increase in the sensitivity of spinal nociceptive system, and smaller decrease in local muscle blood oxygenation response in both the ipsilateral and the contralateral TA, with a greater attenuation being observed for the ipsilateral condition.…”
Section: Introductionmentioning
confidence: 99%